Peningkatan Kepuasan Layanan Prima pada Kantor Imigrasi Kelas I TPI Denpasar, Bali - Krisnayuni, Ni Kadek Prima; Putri, Dewa Ayu Putu Adhiya Garini (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Class I TPI Denpasar Immigration Office is a public service place, where in that environment it is customary to serve many people who come to take care of passports and visas. Public services are expected to be able to provide optimal, proper, and excellent services to the community in carrying them out. The quality of service provided must be considered carefully when carrying out a public service, so that it can provide good comfort for visitors who come and make visitors happy with the services we provide. This can be maintained by implementing excellent service. The sincere service provided by a civil servant to the community, like a servant to his customers, is known as excellent service. (Cucun Supredi et al., 2023). The method used is to conduct observations to see the existing problems, and after that carry out assistance activities in providing good service. This community service activity takes place by becoming a visitor service ambassador which aims to improve services to visitors who come to the Immigration Office. With the results of the discussion that excellent service is the key to the quality of service provided, seen from positive Google reviews, it shows that the Immigration Office has implemented excellent service.